EFECTO DEL ENVEJECIMIENTO ACELERADO POR TEMPERATURA EN 3 TIPOS DIFERENTES DE CERVEZAS ALE (RUBIA DE TRIGO, ROJA Y NEGRA) - DUEÑAS INTRIAGO, SANDY MIKAELA (2025)
The research analyzed accelerated aging in Ale beers (wheat blonde, red, and dark) through a three-factor AxBxC design, considering the type of beer, aging time (4, 7, and 9 days), and storage temperature (23 °C, 26 °C, and 30 °C), in addition to studying their microbiological and sensory behavior. It was determined that the best physicochemical treatment for Ale beers (wheat blonde, red, and dark) was achieved at 23 °C, while the best sensory response was recorded at 26 °C